2001
DOI: 10.1095/biolreprod65.3.799
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II and Atrial Natriuretic Peptide in the Cow Oviductal Contraction In Vitro: Direct Effect and Local Secretion of Prostaglandins, Endothelin-1, and Angiotensin II

Abstract: Angiotensin II (Ang II) and atrial natriuretic peptide (ANP) may be involved in local regulation of the oviductal contraction during the estrous cycle. Thus, the in vitro effects of Ang II and ANP on the secretion and contraction of bovine oviduct during the follicular, postovulatory, and luteal phases were investigated. An in vitro microdialysis system (MDS) was utilized to determine the intraluminal release of prostaglandins (PGs), Ang II, and endothelin-1 (ET-1) from the bovine oviducts as well as to observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
37
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 36 publications
3
37
0
Order By: Relevance
“…Moreover, luteinizing hormone (LH) stimulates e production and release of these hormones by the bovine oviduct during this period, and estradiol-17β (E2) exerts a synergistical effect on this LH action [11]. Thus, it has been speculated that Ang II production is stimulated by LH and ovarian steroids in the regulation of the peak oviductal contractions responsible for rapid gamete transport to the fertilization site [6].The Ang II concentration increases dramatically in the ovarian venous plasma after the LH surge, [12] and follicular Ang II rises during the LH surge [12]. Moreover, E2 increases Ang II production in microvascular endothelial cells from the bovine corpus luteum in vitro [13] and induces Ang II-R expression in bovine thecal cells [14].…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, luteinizing hormone (LH) stimulates e production and release of these hormones by the bovine oviduct during this period, and estradiol-17β (E2) exerts a synergistical effect on this LH action [11]. Thus, it has been speculated that Ang II production is stimulated by LH and ovarian steroids in the regulation of the peak oviductal contractions responsible for rapid gamete transport to the fertilization site [6].The Ang II concentration increases dramatically in the ovarian venous plasma after the LH surge, [12] and follicular Ang II rises during the LH surge [12]. Moreover, E2 increases Ang II production in microvascular endothelial cells from the bovine corpus luteum in vitro [13] and induces Ang II-R expression in bovine thecal cells [14].…”
mentioning
confidence: 99%
“…Moreover, our recent reports revealed that TNFα [7,8], VEGF [29] and atrial natriuretic peptide (ANP) [6] stimulates the production and release of PGE2, PGF2α and ET-1in the bovine oviduct [7,8,11,29]. Also, Ang II stimulate PGE2, PGF2α and ET-1 release [6]. Thus, Ang II appears to be a local mediator for TNFα, VEGF and ANP to stimulate PGE2, PGF2α and ET-1 release from the oviduct, in addition to acting directly on oviductal smooth muscle [11].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, several studies have revealed that the preovulatory surge of luteinizing hormone (LH) activates maximum bovine oviductal secretion and contraction [8][9][10][11][12]. Thus, LH may directly stimu late the release of soluble ovid uctal glycosyltransferases, increasing glycosylation and thereby providing the best environment for fertilization, gamete/embryo survival and development.…”
mentioning
confidence: 99%